1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Bi Linear Functionals and Symmetry

  1. Jul 12, 2012 #1
    1. The problem statement, all variables and given/known data

    Show that ## \displaystyle B_1(u,v)=\int_a^b (p(x) u \cdot v + q(x) \frac{du}{dx} \cdot v)dx## is a bilinear functional and is NOT symmetric
    1. The problem statement, all variables and given/known data

    Bilinear relation ##B(\alpha u_1+\beta u_2,v)=\alpha B(u_1,v) +\beta B(u_2,v)## (1)
    ##B(u, \alpha v_1+ \beta v_2)=\alpha B(u,v_1) +\beta B(u,v_2)## (2)

    Symmetry ##B(u,v)=B(v,u)##

    where u and v are vectors and ##u\cdot v## is the dot product

    2. Relevant equations

    ##\displaystyle B(\alpha u_1+\beta u_2,v)=\int_a^b \left( p(x)(\alpha u_1+\beta u_2) \cdot (v)+q(x) \frac{d}{dx} (\alpha u_1+\beta u_2) \cdot v \right) dx##

    ## \displaystyle=\int_a^b \left ((p(x)\alpha u_1 \cdot v+p(x) \beta u_2 \cdot v +q(x) \alpha \frac{d u_1}{dx} \cdot v+q(x) \beta \frac{ d u_2}{dx}\cdot v \right) dx## which after re-arranging gives

    ##\alpha B(u_1,v) +\beta B(u_2,v)##

    Similarly for the RHS of (2). THis shows it is bilinear.

    However, I am not sure I understand the concept of symmetry in this case that it is not symmetric?
  2. jcsd
  3. Jul 12, 2012 #2
    You just need to show that B(u,v) ≠ B(v,u), aka showing that it is not true that B(u,v)=B(v,u)
    There's nothing more than plugging in involved here, what is it exactly you're having problems with?
  4. Jul 12, 2012 #3
    Is ##B(v,u)## to be written in the form ##B(\alpha v_1+\beta v_2,u)##?

    I dont get the idea of interchanging the vectors since ##u \cdot v= v \cdot u##....?
  5. Jul 12, 2012 #4
    You've already shown that it's bilinear so you now only need to show that it's not symmetric;
    Since you're only trying to show that B isn't symmetric you don't need to bother about plugging linear combinations in, you only need to compare B(u,v) with B(v,u).

    If B is symmetric, by definition, B(u,v) = B(v,u). You want to show that this is not the case.

    For example;
    Take [itex]A(x,y) = x^2 + y^2 [/itex] then
    [itex]A(x,y) = x^2 + y^2 = y^2 + x^2 = A(y,x)[/itex]
    So A is symmetric

    Take [itex]C(x,y) = x - y[/itex] then
    [itex]C(x,y) = x - y = -(y-x) = -C(y,x)[/itex]
    So C is NOT symmetric (if something has this property [itex]C(x,y) = - C(y,x)[/itex] it's called 'skew-symmetric')

    Take [itex]D(x,y) = 2x + y[/itex] then
    [itex]D(x,y) = 2x + y ≠ 2y +x = D(y,x)[/itex]

    Or you could even say, if F is symmetric then [itex]F(x,y) - F(y,x) = 0[/itex]
    then you'd get
    [itex]A(x,y) - A(y,x) = x^2 + y^2 - y^2 - x^2 = 0[/itex]
    skew-symmetric (a subset of 'not symmetric');
    [itex]C(x,y) - C(y,x)= x - y - y + x) = 2x - 2y = 2C(x,y)[/itex]
    not symmetric
    [itex]D(x,y) - D(y,x)=2x + y - 2y -x = x - y ≠ 0[/itex]

    I know these are pretty simple examples but can you see the idea I'm trying to convey here?

    Actually, I just missed that last part so I guess the above was a little pointless -.-

    if you look at B, there's another dot product which WILL change if you interchange u and v
    Last edited: Jul 12, 2012
  6. Jul 12, 2012 #5
    This conveys the idea very nicely thanks. I have one quick question before I look at it properly tomorrow and apply it to the original question.

    Why do you write ##D(y,x)=2y+x##?
    I would have thought that ##D(y,x)=y+2x##?
    Isn't one just interchanging the variables?
  7. Jul 12, 2012 #6


    Staff: Mentor

    This is just basic function evaluation. If D(x, y) = 2x + y, then D(y, x) = 2y + x. The '2' coefficient goes with the first argument of the function, which in D(y, x) is y.
  8. Jul 12, 2012 #7
    nono, if I have [itex]D(x,y) = 2x + y[/itex] I'm pretty much saying 'take two times the first argument and add one times the second argument', using this [itex]D(y,x)[/itex] says 'take two times y and add one times x' which is 2y + x
  9. Jul 12, 2012 #8
    Thanks guys, that I didn't know..or perhaps it slowly crept out of my memory! I will look at the rest when I can.
  10. Jul 15, 2012 #9
    ## \displaystyle B_1(u,v)=\int_a^b (p(x) u \cdot v + q(x) \frac{du}{dx} \cdot v)dx \ne \int_a^b(p(x) v \cdot u+q(x) \frac{dv}{dx} \cdot u)dx=B_2(v,u)##..ok?
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook